Entanglement dynamics of three-qubit states in noisy channels - Siomau, Michael; Fritzsche, Stephan (The European physical journal. D, Atomic, molecular, optical and plasma physics, 2010)
We study entanglement dynamics of the three-qubit systemwhich is initially prepared in pure Greenberger-Horne-Zeilinger(GHZ) or W state and transmitted through one of the Pauli channels$σ_z$, $σ_x$, $σ_y$or the depolarizing channel.With the help of the lower bound for three-qubit concurrence we showthat the W state preserves more entanglement than the GHZ state intransmission through the Pauli channel $σ_z$. For the Paulichannels $σ_x$, $σ_y$and the depolarizing channel,however, the entanglement of the GHZ state is more resistant againstdecoherence than the W-type entanglement. We also briefly discusshow the accuracy of the lower bound approximation depends on therank of the density matrix under consideration.
Gesehen am 07.08.2023